Severe hyperchloremic metabolic acidosis with SGLT2 inhibitors in patients with urinary diversion - Carolina Gomes; João Barbosa Barroso; Ana Isabel Oliveira; Sofia Guerreiro Cruz; Liliana Cunha; Ana Azevedo (Nefrología)
Urinary diversion after cystectomy using autologous intestinal segments has been the gold standard treatment in several urinary tract diseases. The most frequent metabolic consequence is hyperchloremic metabolic acidosis, due to ammonium hydrogen and chloride ions absorption in exchange for the excretion of bicarbonate and sodium ions in the bowel conduit.Sodium-glucose co-transporter-2 (SGLT2) inhibitors are a class of antihyperglycemic agents that block the reabsorption of filtered glucose in the renal proximal convoluted tubules, promoting greater urinary glucose and sodium excretion.The authors describe two cases of patients with bowel conduit and mild/severe hyperchloremic metabolic acidosis, after starting SGLT2 inhibitors. Both were presented with mild acute kidney injury, moderate hyperglycemia, normal ketoacids, normal lactate and normal anion gap. Clinical and laboratory normalization were reached after this drug was withdrawn and fluid support therapy was applied.We hypothesize that SGLT2 inhibitors could exacerbate chronic hyperchloremic metabolic acidosis in these patients, by enhance sodium loss and volume depletion, subsequent acute kidney injury (AKI), increase renal chloride elimination due to sodium loss and subsequent chloride/bicarbonate bowel exchange. Rebound hyperglycemia due to bowel absorption and bicarbonate renal elimination through Na+−H+exchanger 3 (NHE3) suppression, could also contribute. This association needs further investigation. Resumen: La derivación urinaria tras una cistectomía utilizando segmentos intestinales autólogos ha sido el tratamiento de referencia en diversas enfermedades del tracto urinario. La consecuencia metabólica más frecuente es la acidosis metabólica hiperclorémica, que resulta de la absorción de iones amonio, hidrógeno y cloruro a cambio de la excreción de iones bicarbonato y sodio en el conducto intestinal.Los inhibidores del cotransportador sodio-glucosa 2 (SGLT2) son una clase de agentes antihiperglucemiantes que bloquean la reabsorción de glucosa filtrada en los túbulos renales proximales contorneados, lo que favorece un aumento de la glucosa urinaria.Los autores describen dos casos de pacientes con derivación intestinal y acidosis metabólica hiperclorémica (leve a grave) tras iniciar tratamiento con inhibidores de SGLT2. Ambos pacientes presentaban lesión renal aguda leve, hiperglucemia moderada, cetoácidos normales, lactato normal y brecha aniónica normal. La normalización clínica y de los parámetros de laboratorio se logró tras la interrupción de este fármaco y la administración de terapia de soporte con fluidos.Nuestra hipótesis es que los inhibidores de SGLT2 podrían exacerbar la acidosis metabólica hiperclorémica crónica en estos pacientes, al aumentar la pérdida de sodio y la depleción de volumen, lo que podría provocar lesión renal aguda (LRA) secundaria. Esto, a su vez, favorecería el aumento de la eliminación renal de cloruro debido a la pérdida de sodio y el posterior intercambio intestinal de cloruro/bicarbonato.Asimismo, podría contribuir la hiperglucemia de rebote debido a la absorción intestinal de glucosa y la eliminación renal de bicarbonato a través de la inhibición del intercambiador Na+-H+3 (NHE3). Es necesario continuar investigando esta asociación.